PEMUSNAHAN BARANG BUKTI NARKOTIKA OLEH KEJAKSAAN NEGERI NIAS SELATAN ATAS PUTUSAN NOMOR 99/PID.SUS/2022/PN GST - Doretius Rintoasuandulo Zamili (Jurnal Panah Hukum, 2025)
Law is a collection of regulations that must be obeyed by everyone in society, with the threat of having to compensate for losses or receive punishment. Basically, as stated in the 1945 Constitution of the Republic of Indonesia in Article 1 paragraph (3), this means that all citizens and administrators must comply with the applicable legal rules. The concept of a rule of law can be idealized in that it must be the commander in chief in all the dynamics of state life. is law, not politics or economics. The research aims to find out how narcotics evidence is destroyed by the South Nias District Prosecutor's Office. The type of research used is sociological legal research. Sociological legal research is legal research in the form of empirical studies to discover the application and truth of law in society. The aim of sociological legal research is to find information about something that happened. The type of approach used is descriptive using initial data as a comparison. The data collection technique is library research. This research data analysis is a descriptive research specification, which means research that aims to describe research about something that is valid at a certain time. Based on the research findings and discussion in the research, the researcher can conclude that the South Nias District Prosecutor's Office carried out the destruction of narcotics evidence because it had permanent legal force based on the court's decision. From research findings, the South Nias District Prosecutor's Office destroys narcotics evidence twice a year. Meanwhile, according to statutory regulations in the implementation of the destruction of narcotics evidence, it must be destroyed no later than 7 (seven) days after a court decision is made which has permanent legal force. The policy taken by the South Nias District Prosecutor's Office in destroying narcotics evidence is contrary to the law which means that they should not wait for a large amount of confiscated evidence to be destroyed. The South Nias District Prosecutor's Office is not guided by the mandate of the law in carrying out the stages of the process of destroying confiscated objects.